2014
DOI: 10.1016/j.tig.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Genome typing of nonhuman primate models: implications for biomedical research

Abstract: The success of personalized medicine rests on understanding the genetic variation between individuals. Thus, as medical practice evolves and variation among individuals becomes a fundamental aspect of clinical medicine, a thorough consideration of the genetic and genomic information concerning the animals used as models in biomedical research also becomes critical. In particular, nonhuman primates (NHPs) offer great promise as models for many aspects of human health and disease. These are outbred species exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 59 publications
1
31
0
1
Order By: Relevance
“…The successful identification of genetic polymorphisms in the LDLR gene of the hyporesponder cynomolgus macaque suggests a link between genetic variation and the nature of response to the atherogenic diet, although it still requires further confirmation of using more number of hyporesponder animals and an explanation of its underlying mechanism. This supports an important principle in animal modeling that common genetic variations in experimental animals can influence the results of biomedical experiments (Haus et al, 2014).…”
Section: Genetic Variationsupporting
confidence: 69%
“…The successful identification of genetic polymorphisms in the LDLR gene of the hyporesponder cynomolgus macaque suggests a link between genetic variation and the nature of response to the atherogenic diet, although it still requires further confirmation of using more number of hyporesponder animals and an explanation of its underlying mechanism. This supports an important principle in animal modeling that common genetic variations in experimental animals can influence the results of biomedical experiments (Haus et al, 2014).…”
Section: Genetic Variationsupporting
confidence: 69%
“…Thus, prospective studies can be performed on these animals using a ligature‐induced model of disease to assess the interactions of the microbiome and host responses during the initiation and progression of periodontitis to better understand these factors as explanatory variables in disease extent and severity in the human population. Furthermore, recent studies have demonstrated similarities and overlap in SNPs between humans and macaques, as well as clear epigenetic evidence for altered biological functions in these nonhuman primates . Thus, this model may also provide access to a better understanding of the genetic contributors to periodontitis susceptibility.…”
Section: Discussionmentioning
confidence: 95%
“…Perbandingan genomik (comparative genomics) yang lebih ekstensif harus dilakukan antara genom manusia dan primate non-manusia supaya mendapatkan informasi lebih valid untuk mengurangi noise latar belakang genetic (Haus et al, 2014) . Pada akhirnya, penggunaan metode prediksi gen yang lebih akurat dan efisien dibanding yang disediakan oleh Refseq/ GenBank memang harus diutamakan untuk anotasi gen yang lebih baik (Hoff dan Stanke 2013;Souvorov et al, 2010) …”
Section: Pembahasanunclassified